Modified recycled aggregate high-temperature-resistant ultrahigh-ductility concrete and preparation method thereof

Through the combination technology of nano SiO2 impregnation and multiple fibers, the modified regenerated aggregate concrete exhibits excellent crack resistance and durability at high temperatures, solving the problems of high-temperature explosion and fly ash pollution in the existing technology, realizing construction Efficient reuse of garbage and improvement of environmental protection performance.

CN119241180APending Publication Date: 2025-01-03SHIJIAZHUANG TIEDAO UNIV

Patent Information

Application Number
CN202411765641.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing concrete is prone to bursting and peeling at high temperatures, has low tensile strength and poor crack resistance, and the landfill method of fly ash occupies land and is seriously polluted. Existing recycled aggregate concrete has shortcomings in tensile and high temperature resistance. .

Method used

Modified regenerated aggregates are prepared by nano-SiO2 impregnation treatment, and combined with the multiple fiber coupling of dechlorinated fly ash, multi-walled carbon nanotubes, polyethylene fibers and calcium carbonate whiskers, and high-temperature resistant ultra-high ductility concrete. , improve its strength, toughness and durability.

Benefits of technology

It has achieved significant improvement in the durability and crack resistance of concrete at high temperatures, reduced the amount of cement used, reduced the cost of fly ash disposal, realized the green reuse of construction waste and domestic waste, and significantly improved the compressive resistance and resistance of concrete. Tensile strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides modified recycled aggregate high-temperature-resistant ultrahigh-ductility concrete and a preparation method thereof, and belongs to the technical field of cement-based building materials, the concrete is prepared from the following raw materials in parts by weight: 300-370 parts of cement, 340-420 parts of fly ash, 20-35 parts of dechlorinated fly ash, 600-720 parts of modified recycled coarse aggregate, 280-510 parts of quartz sand, 10-25 parts of polyethylene fiber and 0.5-1 part of multiwalled carbon nanotube. The concrete is prepared from the following components in parts by weight: 50-60 parts of calcium carbonate whiskers, 160-210 parts of water, 3-8 parts of polycarboxylate superplasticizer and 0.5-2 parts of thickener. By adopting the modified recycled aggregate high-temperature-resistant ultrahigh-ductility concrete and the preparation method thereof, the green and environment-friendly high-temperature-resistant ultrahigh-ductility concrete with excellent performance is prepared, and the reutilization of construction wastes and household wastes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a modified recycled aggregate high-temperature resistant ultra-high ductility concrete and a preparation method thereof. Background Art

[0002] In addition to construction waste, the pollution caused by urban domestic waste to the environment is also becoming increasingly serious. Since waste incineration technology can effectively reduce the volume of waste, energy recovery has become an important research and development direction for waste resource utilization and volume reduction treatment technology in my country. Fly ash is one of the products after burning waste. It refers to the residue collected in flue gas purification systems and heat recovery systems such as economizers and boilers. Although the current method of fly ash disposal in various countries mainly adopts direct landfill after cement solidification, this solidification and landfill method not only occupies a large amount of land resources, but also the harmful heavy metals and organic matter in the fly ash will seep into the soil and groundwater, causing pollution to the soil and groundwater. If the appropriate amount of dechlorinated fly ash can be used in the production of concrete, it will turn waste into treasure, which will not only alleviate the pressure of fly ash on the environment but also realize the circular development of the building materials industry, which has good economic, social and environmental significance.

[0003] Recycled coarse aggregate is generally crushed from discarded concrete components. Its surface is covered with a layer of cement mortar with many edges and corners. Cracks will also appear inside during the crushing process, which makes recycled coarse aggregate have certain disadvantages compared with natural coarse aggregate, such as large crushing index, low density, high water absorption, etc., which have an adverse effect on the safety of the structure. In addition, ordinary concrete has defects such as low tensile strength, poor crack resistance, and large shrinkage deformation. It may also burst and spall under high temperature. In a fire, concrete will also break into scattered lime and release CO 2 Gas, resulting in a decrease in structural strength, ultimately causing building damage and casualties. Therefore, improving the high temperature bearing capacity of concrete will greatly reduce the damage caused by fire.

[0004] The patent with publication number CN117263624A (Patent 1) discloses a recycled aggregate concrete and its preparation method. This method modifies the recycled aggregate, strengthens the coordination between the reinforcing agent and the modified recycled aggregate, forms a coating, reduces the entry of water into the modified recycled aggregate, and improves the strength of the concrete. This invention only involves the compressive properties of the recycled aggregate concrete, with the highest 28-day compressive strength reaching 49.9 MPa, but does not disclose its tensile properties and high temperature resistance, and the excellent mechanical properties are single.

[0005] The patent with publication number CN116639918A (Patent 2) discloses a method for preparing reinforced recycled aggregate concrete. This method prepares concrete by pre-treating the waste concrete, removing smaller particles, dust and attached mortar, etc. to obtain reinforced aggregate. This invention also only involves the compressive performance of recycled aggregate concrete. Sodium silicate is used to form a glassy covering film on the surface of the recycled aggregate, and the pores and microcracks of the recycled aggregate are effectively filled, making the concrete more compact, so that the compressive strength of the concrete is greatly improved. However, the concrete prepared by this method has low toughness and low crack resistance, which makes it easy to cause brittle fracture, thereby affecting the durability of the concrete. This invention also does not disclose its tensile properties and high temperature resistance. Summary of the invention

[0006] The purpose of the present invention is to provide a modified recycled aggregate high temperature resistant ultra-high ductility concrete and a preparation method thereof, by using nano-SiO 2 The recycled coarse aggregate is modified by impregnation, and combined with recycled dechlorinated fly ash, multi-walled carbon nanotubes, and multiple fiber coupling effects of polyethylene fibers and calcium carbonate whiskers, a green, environmentally friendly, high-performance, high-temperature resistant and ultra-high ductility concrete is prepared, realizing the reuse of construction waste and domestic waste.

[0007] To achieve the above object, the present invention provides a modified recycled aggregate high temperature resistant ultra-high ductility concrete, which is composed of the following raw materials in parts by weight: 300-370 parts of cement, 340-420 parts of fly ash, 20-35 parts of dechlorinated fly ash, 600-720 parts of modified recycled coarse aggregate, 280-510 parts of quartz sand, 10-25 parts of polyethylene fiber, 0.5-1 part of multi-walled carbon nanotubes, 50-60 parts of calcium carbonate whiskers, 160-210 parts of water, 3-8 parts of polycarboxylic acid water reducer, and 0.5-2 parts of thickener; The preparation method of modified recycled coarse aggregate is as follows: a. Recycle the 5~10mm waste concrete after crushing, i.e. recycled coarse aggregate; b. Using nano-SiO 2 Preparation of nano-SiO with a water-binder ratio of 0.5 by using solution, polycarboxylate water-reducing agent, cement and pure water 2 Strengthening slurry, in which nano-SiO 2 Solution: polycarboxylate water reducer: cement = 1:1:100; c. Recycled coarse aggregate and nano-SiO 2 The enhanced slurry was mixed and stirred for 3 to 5 times. After each stirring for 1 minute, the mixture was allowed to stand for 1 minute. After the last stirring, the coated nano-SiO 2 The recycled coarse aggregate of the reinforced slurry is fished out; d. Use a sieve with a pore size of 5 mm to remove excess nano-SiO2 Strengthen the slurry, spread the recycled coarse aggregate on a dry and clean wooden board, and ventilate and dry it at a temperature of 20±2°C and a relative humidity of 64%±5%, turning it over every 2 hours until the recycled coarse aggregate is in a naturally air-dried state, thereby obtaining the modified recycled coarse aggregate.

[0008] The recycled coarse aggregate contains a large number of needle-like particles, and the surface of the recycled coarse aggregate contains a large amount of hardened mortar, which will lead to low density, high water absorption, high porosity and poor durability of the recycled coarse aggregate. These disadvantages will directly lead to poor performance of concrete containing recycled coarse aggregate. The present invention recycles the crushed waste concrete, and then uses nano-SiO 2 The recycled coarse aggregate is impregnated with the solution, and the dry recycled coarse aggregate is repeatedly immersed in the well-dispersed nano-SiO 2 In the solution, nano-SiO 2 The solution will be absorbed by the dry aggregate, and in this process, the nano-SiO 2 The particles will be deposited on the surface of the aggregate, and some particles will even penetrate a few microns below the surface of the aggregate, and then react with calcium hydroxide to form a (CSH) gel. Therefore, the porous surface of the recycled coarse aggregate can be densified by this coating method through a rapid volcanic ash reaction and a filling effect. The porous interface transition zone between the old mortar and the old aggregate and between the old aggregate and the new mortar can also be densified by the filling effect of the volcanic ash and nanoparticle layer on the surface of the aggregate. The recycled aggregate and the new mortar will be firmly combined, thereby improving the strength and durability of the recycled coarse aggregate concrete. The present invention utilizes the modified recycled coarse aggregate in concrete to prepare ultra-high ductility concrete that meets the construction requirements, thereby realizing the reuse of construction waste.

[0009] Preferably, the cement is one of ordinary Portland cement and composite Portland cement, and the 28-day compressive strength is not less than 42.5 MPa.

[0010] Preferably, the fly ash is Class F fly ash, with a particle size range of 50-400 μm and a specific surface area of ​​not less than 400 m 2 / kg.

[0011] Preferably, the particle size of dechlorinated fly ash is less than 150 μm, and the specific surface area is not less than 17.8 m 2 / g, average pore diameter is 15.2μm, density is 2.31g / cm 3 .

[0012] The present invention adds dechlorinated fly ash when preparing modified recycled aggregate high temperature resistant ultra-high ductility concrete. The fly ash is first dried, that is, the fly ash is homogenized and then placed in an oven for drying at 105°C for 2 hours, and then directly mixed into the concrete instead of part of the cement.

[0013] On the one hand, the main component of dechlorinated fly ash is CaO 2 -SiO 2 -Al 2 O 3 -Fe 2 O 3 The system is very similar to commonly used auxiliary cementitious materials such as blast furnace slag and fly ash, and it contains more heavy metal elements. It can be applied to the preparation of ultra-high ductility concrete to greatly improve its high temperature resistance. At the same time, the harmful heavy metal elements in dechlorinated fly ash can be effectively solidified through the wrapping effect of cement concrete. On the other hand, directly adding dechlorinated fly ash to concrete instead of cement of equal mass not only saves a lot of fly ash disposal costs but also saves the quality of cement used, thereby reducing the cost of cement concrete products.

[0014] Preferably, the polyethylene fiber has a length of 12 to 36 mm, a diameter of 20 to 40 μm, an aspect ratio of not less than 600, an elastic modulus of not less than 100 GPa, and a tensile strength of not less than 2800 MPa.

[0015] The present invention adopts polyethylene fiber to prepare modified recycled aggregate high temperature resistant ultra-high ductility concrete. The polyethylene fiber has high tensile strength and tensile elastic modulus, which is beneficial to achieving high ductility, high durability and good crack control behavior of ultra-high ductility concrete. In addition, the volume fraction of polyethylene fiber is about 1.5-2.5% of the total volume of concrete, and this amount of fiber can achieve the high ductility requirement of concrete. Polyethylene fiber will melt at high temperature, providing a migration channel for water vapor inside the modified recycled aggregate high temperature resistant ultra-high ductility concrete structure, so that the steam pressure in the component is released, effectively suppressing the high temperature burst phenomenon, and improving the high temperature resistance of recycled aggregate concrete. Moreover, the hydrophobic property of polyethylene fiber can significantly increase the supplementary residual energy during the fiber extraction process, which helps to achieve strain hardening and multi-crack cracking of modified recycled aggregate high temperature resistant ultra-high ductility concrete.

[0016] Preferably, the multi-walled carbon nanotubes have a diameter of 10-25 nm, a length of 3-10 μm, a purity of not less than 97.5 wt.%, and a specific surface area of ​​170-250 m 2 / g.

[0017] The present invention adopts multi-walled carbon nanotubes to prepare modified recycled aggregate high temperature resistant ultra-high ductility concrete. Multi-walled carbon nanotubes are one of the effective components for improving the mechanical properties of cement concrete. This material belongs to one-dimensional nanomaterials and has excellent mechanical properties. Its tensile strength can reach up to 200GPa and its elastic modulus can reach 1TPa. The polyethylene fiber, calcium carbonate whisker and multi-walled carbon nanotubes used in the present invention can play a bridging role in concrete together. This bridging effect can make the carbon nanotubes uniformly dispersed in the concrete bear the load, reduce the stress of the concrete, effectively delay the net cracking time of the concrete, and improve the crack resistance of the concrete. The diameter of the carbon nanotubes used in the present invention is 10nm~25nm. The carbon nanotubes can fill the micropores in the concrete, reduce the content of the micropores, thereby reducing the capillary pressure inside the concrete, and further reduce the shrinkage strain of the concrete.

[0018] Preferably, the calcium carbonate whisker has a length of 0.05-0.08 mm, a diameter of 0.5-1.2 μm, and a tensile strength of >3 GPa.

[0019] The present invention mixes polyethylene fibers, multi-walled carbon nanotubes, and calcium carbonate whiskers to enhance toughness and improve its high temperature resistance. Calcium carbonate whiskers are micron-scale fibers. The efficient bridging effect between polyethylene fibers and calcium carbonate whiskers inhibits the generation and expansion of micro cracks in recycled aggregate concrete from both macroscopic and microscopic perspectives, reduces the number of harmful pores in modified recycled aggregate high temperature resistant ultra-high ductility concrete, and refines the pore structure. Secondly, the multiple fibers and concrete are added to jointly withstand tensile stress through bonding and mechanical bite forces, thereby improving the bearing capacity of concrete, reducing the size of the structural cross-section to a certain extent, and preventing external moisture from invading by crack blocking, thereby improving the compactness of the cement matrix, and making the prepared concrete have higher compressive strength and tensile strength.

[0020] In addition, calcium carbonate whiskers are stable at high temperatures and can effectively reduce the phenomenon of reduced high-temperature mechanical properties and strength failure of modified recycled aggregate ultra-high ductility concrete due to the melting of fibers and the generation of water vapor escape channels at high temperatures. Polyethylene fibers, multi-walled carbon nanotubes, and calcium carbonate whiskers work together to improve the high-temperature resistance of modified recycled aggregate ultra-high ductility concrete.

[0021] Preferably, the thickener is polyacrylamide.

[0022] The present invention also provides a method for preparing modified recycled aggregate high temperature resistant ultra-high ductility concrete, comprising the following steps: S1. First, weigh the cement, fly ash, dechlorinated fly ash, quartz sand and polycarboxylate water reducer in parts by weight and add them into a mixer and stir slowly to mix the dry materials evenly; S2. Add water to the mixer, and after the dry material is liquefied, add the thickener and stir slowly; S3, adding polyethylene fibers, multi-walled carbon nanotubes, and calcium carbonate whiskers into a blender and rapidly stirring; S4. Add the modified recycled coarse aggregate into the mixer and stir it evenly at a slow speed; S5. Pour the mixed slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure at 20-25°C for 28 days to obtain high temperature resistant ultra-high ductility concrete.

[0023] Preferably, the slow stirring time in step S1 is 1 to 3 min, the slow stirring time in step S2 is 1 to 4 min, the fast stirring time in step S3 is 2 to 4 min, the slow stirring time in step S4 is 3 to 5 min, and the vibration time in step S5 is 3 to 4 min; The speed of slow stirring is 100~125r / min, and the speed of fast stirring is 175~210r / min.

[0024] Therefore, the present invention adopts the above-mentioned modified recycled aggregate high temperature resistant ultra-high ductility concrete and its preparation method, and the technical effects are as follows: (1) The polyethylene fibers, multi-walled carbon nanotubes, and calcium carbonate whiskers of the present invention help to achieve strain hardening and multi-crack cracking behavior of recycled aggregate concrete. The fibers will melt at high temperatures, providing a migration channel for water vapor inside the modified recycled aggregate ultra-high ductility concrete structure, effectively suppressing high-temperature bursting and improving the high-temperature resistance of recycled aggregate concrete.

[0025] (2) The present invention uses nano-SiO 2 The recycled coarse aggregate is modified by solution impregnation. The porous surface of the recycled coarse aggregate is densified through rapid volcanic ash reaction and filling effect. At the same time, the porous interface transition zone between the old mortar and the old aggregate and between the old aggregate and the new mortar is also densified, thereby improving the strength and durability of the recycled coarse aggregate concrete.

[0026] (3) The present invention utilizes modified recycled coarse aggregate and dechlorinated fly ash, which effectively solidifies harmful heavy metal elements in dechlorinated fly ash on the one hand, and reduces the amount of cement used on the other hand, saving fly ash disposal costs and reducing the cost of cement concrete products. The recycling of construction waste and domestic waste is achieved. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further illustrated by the following examples.

[0028] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0029] Unless otherwise specified, the raw materials used in the examples are all well-known, commercially available chemical raw materials.

[0030] Among them, the cement is 42.5 ordinary Portland cement, the fly ash is F-grade fly ash, the polyethylene fiber length is 12~36mm, the multi-walled carbon nanotube diameter is 10~25nm, the length is 3~10μm, the calcium carbonate whisker length is 0.05~0.08mm, the diameter is 0.5~1.2μm, the water reducer is polycarboxylic acid high-efficiency water reducer, and the thickener is polyacrylamide.

[0031] The preparation method of modified recycled coarse aggregate is as follows: a. Recycling the 5-10 mm waste concrete after crushing; b. Using nano-SiO 2 Preparation of nano-SiO with a water-binder ratio of 0.5 by using solution, polycarboxylate water-reducing agent, cement and pure water 2 Strengthening slurry, in which nano-SiO 2 Solution: polycarboxylate water reducer: cement = 1:1:100; c. Recycled coarse aggregate and nano-SiO 2 The enhanced slurry was mixed and stirred for 3 to 5 times. After each stirring for 1 min, the mixture was allowed to stand for 1 min. After the last stirring, the coated nano-SiO 2 The recycled coarse aggregate of the reinforced slurry was removed; d. The excess cement nano-SiO 2 Strengthen the slurry, spread the recycled coarse aggregate flat on a dry and clean wooden board, and ventilate and dry it at a temperature of 20±2°C and a relative humidity of 64%±5%, turning it over every 2 hours until the recycled coarse aggregate is in a naturally air-dried state.

[0032] In order to characterize the technical effect of the present invention, the mechanical properties of the concrete after 28 days of curing were tested.

[0033] Embodiment 1 The modified recycled aggregate high temperature resistant ultra-high ductility concrete is composed of the following raw materials in parts by weight: 360 parts of cement, 406 parts of fly ash, 25 parts of dechlorinated fly ash, 720 parts of modified recycled coarse aggregate, 285 parts of quartz sand, 20 parts of polyethylene fiber, 0.5 parts of multi-walled carbon nanotubes, 53 parts of calcium carbonate whiskers, 198 parts of water, 3 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0034] After testing, the modified recycled aggregate high temperature resistant and ultra-high ductility concrete has a compressive strength of 56.3MPa, a tensile strength of 5.27MPa, and a tensile strain capacity of 6.93% under normal temperature conditions; after treatment at 200℃, the compressive strength is 41.6MPa, the tensile strength is 4.02MPa, the tensile strain capacity is 0.89%, the mass loss rate is 9.78%, and the specimen maintains good integrity; after treatment at 400℃, the compressive strength is 33.4MPa, the tensile strength is 1.75MPa, the tensile strain capacity is 0.08%, the mass loss rate is 16.23%, and the specimen maintains good integrity.

[0035] Embodiment 2 The modified recycled aggregate high temperature resistant ultra-high ductility concrete is composed of the following raw materials in parts by weight: 350 parts of cement, 395 parts of fly ash, 24 parts of dechlorinated fly ash, 700 parts of modified recycled coarse aggregate, 346 parts of quartz sand, 15 parts of polyethylene fiber, 0.5 parts of multi-walled carbon nanotubes, 54 parts of calcium carbonate whiskers, 192 parts of water, 5 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0036] After testing, the modified recycled aggregate high temperature resistant and ultra-high ductility concrete has a compressive strength of 54.6MPa, a tensile strength of 5.38MPa, and a tensile strain capacity of 6.48% under normal temperature conditions; after treatment at 200℃, the compressive strength is 43.1MPa, the tensile strength is 3.75MPa, the tensile strain capacity is 1.07%, the mass loss rate is 8.95%, and the specimen maintains good integrity; after treatment at 400℃, the compressive strength is 30.4MPa, the tensile strength is 1.39MPa, the tensile strain capacity is 0.07%, the mass loss rate is 15.53%, and the specimen maintains good integrity.

[0037] Embodiment 3 The modified recycled aggregate high temperature resistant ultra-high ductility concrete is composed of the following raw materials in parts by weight: 305 parts of cement, 344 parts of fly ash, 22 parts of dechlorinated fly ash, 610 parts of modified recycled coarse aggregate, 503 parts of quartz sand, 15 parts of polyethylene fiber, 0.5 parts of multi-walled carbon nanotubes, 54 parts of calcium carbonate whiskers, 168 parts of water, 5 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0038] After testing, the modified recycled aggregate high temperature resistant and ultra-high ductility concrete has a compressive strength of 53.8MPa, a tensile strength of 5.12MPa, and a tensile strain capacity of 6.52% under normal temperature conditions; after treatment at 200℃, the compressive strength is 39.7MPa, the tensile strength is 3.83MPa, the tensile strain capacity is 1.14%, the mass loss rate is 8.78%, and the specimen maintains good integrity; after treatment at 400℃, the compressive strength is 32.9MPa, the tensile strength is 1.59MPa, the tensile strain capacity is 0.1%, the mass loss rate is 16.68%, and the specimen maintains good integrity.

[0039] Comparative Example 1 The concrete is composed of the following raw materials in parts by weight: 360 parts of cement, 406 parts of fly ash, 25 parts of dechlorinated fly ash, 720 parts of 5-10 mm recycled coarse aggregate, 285 parts of quartz sand, 20 parts of polyethylene fiber, 0.5 parts of multi-walled carbon nanotubes, 53 parts of calcium carbonate whiskers, 198 parts of water, 3 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0040] After testing, the compressive strength of concrete under room temperature conditions is 42.8MPa, the tensile strength is 4.47MPa, and the tensile strain capacity is 4.56%; after treatment at 200℃, the compressive strength is 31.8MPa, the tensile strength is 2.73MPa, the tensile strain capacity is 0.71%, the mass loss rate is 14.21%, and the specimen maintains good integrity; after treatment at 400℃, the compressive strength is 21.1MPa, the tensile strength is 0.46MPa, the tensile strain capacity is 0.04%, the mass loss rate is 20.24%, and the specimen has bursting phenomenon.

[0041] Comparative Example 2 The concrete is composed of the following raw materials in parts by weight: 360 parts of cement, 406 parts of fly ash, 25 parts of dechlorinated fly ash, 720 parts of modified recycled coarse aggregate, 285 parts of quartz sand, 10 parts of polyethylene fiber, 20 parts of calcium carbonate whisker, 198 parts of water, 3 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0042] After testing, the compressive strength of concrete under room temperature conditions is 38.3MPa, the tensile strength is 3.12MPa, and the tensile strain capacity is 3.24%; after treatment at 200℃, the compressive strength is 25.7MPa, the tensile strength is 1.94MPa, the tensile strain capacity is 0.59%, the mass loss rate is 14.52%, and the specimen has slight cracks; after treatment at 400℃, the compressive strength is 18.7MPa, the tensile strength is 0.51MPa, the tensile strain capacity is 0.03%, the mass loss rate is 21.56%, and the specimen bursts.

[0043] Comparative Example 3 The concrete is composed of the following raw materials in parts by weight: 360 parts of cement, 406 parts of fly ash, 25 parts of dechlorinated fly ash, 720 parts of modified recycled coarse aggregate, 285 parts of quartz sand, 20 parts of polyethylene fiber, 198 parts of water, 3 parts of polycarboxylic acid water reducer, and 1 part of polyacrylamide.

[0044] After testing, it was found that the compressive strength of concrete under normal temperature conditions was 28.8MPa, and brittle failure occurred. The specimen burst after being treated at 200℃; the specimen burst after being treated at 400℃.

[0045] It is worth noting that the contents not elaborated in detail in the present invention are all prior art and are well known to those skilled in the art.

[0046] Therefore, the present invention adopts the above-mentioned modified recycled aggregate high temperature resistant ultra-high ductility concrete and its preparation method, through nano-SiO 2 The recycled coarse aggregate is modified by impregnation, and combined with recycled dechlorinated fly ash, multi-walled carbon nanotubes, and multiple fiber coupling effects of polyethylene fibers and calcium carbonate whiskers, a green, environmentally friendly, high-performance, high-temperature resistant and ultra-high ductility concrete is prepared to achieve the reuse of construction waste and domestic waste.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A modified recycled aggregate high temperature resistant ultra-high ductility concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 300-370 parts of cement, 340-420 parts of fly ash, 20-35 parts of dechlorinated fly ash, 600-720 parts of modified recycled coarse aggregate, 280-510 parts of quartz sand, 10-25 parts of polyethylene fiber, 0.5-1 parts of multi-walled carbon nanotubes, 50-60 parts of calcium carbonate whiskers, 160-210 parts of water, 3-8 parts of polycarboxylic acid water reducer, and 0.5-2 parts of thickener; The preparation method of modified recycled coarse aggregate is as follows: a. Recycle the 5~10mm waste concrete after crushing, i.e. recycled coarse aggregate; b. Prepare nano-SiO2 reinforced slurry with a water-cement ratio of 0.5 using nano-SiO2 solution, polycarboxylate water-reducing agent, cement and pure water, wherein the nano-SiO2 solution: polycarboxylate water-reducing agent: cement = 1:1:100; c. Mix the recycled coarse aggregate and nano-SiO2 reinforced slurry and stir for 3 to 5 times. After each stirring for 1 minute, let the mixture stand for 1 minute. After the last stirring, remove the recycled coarse aggregate wrapped with nano-SiO2 reinforced slurry; d. Use a sieve with a pore size of 5 mm to sieve out excess nano-SiO2 strengthening slurry, spread the recycled coarse aggregate flat on a dry and clean wooden board, and ventilate and dry it at a temperature of 20±2°C and a relative humidity of 64%±5%, turning it over every 2 hours until the recycled coarse aggregate is in a naturally air-dried state, thereby obtaining the modified recycled coarse aggregate.

2. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The cement is one of ordinary silicate cement and composite silicate cement, and its 28-day compressive strength is not less than 42.5MPa.

3. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The fly ash is Class F fly ash, with a particle size range of 50~400μm and a specific surface area of ​​not less than 400m 2 / kg.

4. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: Dechlorinated fly ash particle size <150μm, specific surface area not less than 17.8m 2 / g, average pore diameter is 15.2μm, density is 2.31g / cm 3 .

5. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The length of the polyethylene fiber is 12~36mm, the diameter is 20~40μm, the aspect ratio is not less than 600, the elastic modulus is not less than 100GPa, and the tensile strength is not less than 2800MPa.

6. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The diameter of multi-walled carbon nanotubes is 10~25nm, the length is 3~10μm, the purity is not less than 97.5wt.%, and the specific surface area is 170~250m 2 / g.

7. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The length of calcium carbonate whiskers is 0.05~0.08mm, the diameter is 0.5~1.2μm, and the tensile strength is >3GPa.

8. The modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 1, characterized in that: The thickener is polyacrylamide.

9. A method for preparing the modified recycled aggregate high temperature resistant ultra-high ductility concrete according to any one of claims 1 to 8, characterized in that: The steps include: S1. First, weigh the cement, fly ash, dechlorinated fly ash, quartz sand and polycarboxylate water reducer in parts by weight and add them into a mixer and stir slowly to mix the dry materials evenly; S2. Add water to the mixer, and after the dry material is liquefied, add the thickener and stir slowly; S3, adding polyethylene fibers, multi-walled carbon nanotubes, and calcium carbonate whiskers into a blender and rapidly stirring; S4. Add the modified recycled coarse aggregate into the mixer and stir it evenly at a slow speed; S5. Pour the mixed slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure at 20-25°C for 28 days to obtain high temperature resistant ultra-high ductility concrete.

10. The method for preparing a modified recycled aggregate high temperature resistant ultra-high ductility concrete according to claim 9, characterized in that: The slow stirring time in step S1 is 1 to 3 minutes, the slow stirring time in step S2 is 1 to 4 minutes, the fast stirring time in step S3 is 2 to 4 minutes, the slow stirring time in step S4 is 3 to 5 minutes, and the vibration time in step S5 is 3 to 4 minutes; The speed of slow stirring is 100~125r / min, and the speed of fast stirring is 175~210r / min.

Citation Information

Patent Citations

  • Hybrid fiber regenerated concrete, and preparation thereof

    CN105481308A

  • High-ductility multi-scale fiber reinforced cement-based composite material and preparation method thereof

    CN116874265A

  • Coarse aggregate-containing ductile concrete as well as preparation method and application thereof

    CN118290102A

Cited By

  • Modification method of waste concrete recycled fine aggregate

    CN119912186A

  • High-strength low-temperature-resistant concrete and preparation method thereof

    CN122233729A